Sonic Rhetorics as Ethics in Action: Hidden Temporalities of Sound in Language(s) - Steven B. Katz (Humanities, 2020)
Sonic rhetorics has become a major area of study in the field of rhetoric, as well as composition and literature. Many of the underlying theories of sonic rhetorics are based on post-Heideggerian philosophy, new materialism, and/or posthumanism, among others. What is perhaps similar across these theories of sonic rhetoric is their “turn” from language and the human in general. This short essay explores sonic rhetorics by examining three temporal dimensions found in language. Specifically, the essay focuses on the more obvious sonic dimensions of time in prosody, and then at deeper levels temporal dimensions in a couple of brief but revealing examples from ancient languages (classical Greek, and Biblical Hebrew). Further, this essay suggests some ways in which time is related to ethics in practice and action. For example, just as time is involved in the continuous creation of our increasingly vast, expanding, infinite but bounded universe, Levinas might say that time is necessary to create the ethical space, or perhaps “hypostasis,” one needs for the possibility to encounter “l’autre”—the Other. Beyond prosody, propriety, even kairos, are hidden temporal dimensions of language that may render sonic rhetorics forms of ethical practice.